Macrofauna bentônica profunda em cânions submarinos das bacias do Espírito Santo e Campos - Gama, Rodrigo Novo (2018)
Submarine canyons (canyons) are heterogeneous ecosystems that create distinct landscapes across continental margins. Canyons are globally recognized to host a high diversity and biomass of species and therefore have ecological importance to other continental margin ecosystems. The oceanographic dynamics and the increasing depth naturally shape the biota composition present within them, throughout a complex topography of canyons, which compounds a variability of habitats and ecosystems with specific biotic and abiotic features and act as preferential routes for the transportation and assimilation from greater energy and productivity sites particles to the most stable deep oceanic seabed. In the present work, we sampled and compared the benthic macrofauna from the Watu Norte and Doce canyons in the Espirito Santo basin canyons with canyons Almirante Camara and Grussai from Campos basin. We tested differences between density, composition and diversity of macrofaunal communities along the bathymetry (all canyons, 150 to 1300 meters) and between canyons (latitudinal gradient within each depth range), and compared the effects of canyons along the continental margin compared to adjacent slopes. The “canyon effect” was observed as an increase in density and distinct composition of macrofaunal organisms from the canyons Watu Norte, Doce, Almirante Camara and their adjacent slopes. The differences were mostly related to the shelf break and upper slope (150 – 400m), likely as a consequence of higher organic input and sediment heterogeneity (i.e. disturbance) within canyons at those depths. Canyons also differentiate among themselves at the shelf break and upper slope, presenting differences in density and structure of the macrofaunal assemblages. There was a clear influence of the increasing depth for all canyons and adjacent slopes, negatively related to the heterogeneity and abundance of benthic macrofauna. Overall, polychaetes and peracarid crustaceans dominated the macrofaunal composition in most sample stations, with exception of a greater dominance of molluscs at the upper slope (400m) of Almirante Camara canyon and its adjacent slope H. Further research is necessary for better understanding of the canyons ecological heterogeneity and relation between their physical and biological processes.